Pengaruh Harga Terhadap Keputusan Pembelian Konsumen Pada Nanostore di Kabupaten Subang - Mulyadi (Asosiasi Ahli Administrasi Indonesia, 2022)
This study aims to analyze prices that influence consumer purchasing decisions at nanostores in Subang Regency. Respondents come from nanostore consumers who live in Subang Regency and shop at nanostores in the past month. The total sample of the study amounted to 102 respondents. The study used a quantitative descriptive method and the data was processed using the SPSS 20 program. In addition, the data were analyzed using a simple linear regression test, simple correlation test, hypothesis testing, coefficient of determination, and chi-square test. Hypothesis testing is done through classical and probalistic approaches. The results of quantitative descriptive analysis show that price has a significant effect on consumer purchasing decisions. This shows that consumers in making purchasing decisions pay attention in terms of price. That way, nanostore business owners need to consider the prices set on the products they sell.